Patterns of Care and Outcomes Among Women With Locally Advanced Cervical Cancer Treated With Curative Intent at a Tertiary Center in South Africa - Juliet Maina; Katie E. Lichter; Elana T. Benishay; Jessica George; Michelle Henry; Nazia Fakie; Surbhi Grover (Cancer Medicine)
ABSTRACT Objective Cervical cancer is the leading cause of cancer‐related deaths for women in South Africa. The standard of care treatment for locally advanced cervical cancer (LACC) is external beam radiation followed by brachytherapy with concurrent platinum‐based chemotherapy. There exists a paucity of data regarding the treatment regimens received by women with LACC in South Africa. The aim of this study is to assess the patterns of care and survival for patients with LACC treated with curative intent at a tertiary care center in South Africa. Materials and Methods This is a retrospective review of cervical cancer patients with histologically confirmed LACC (stage IB2—IVA) who underwent radiation with curative intent at Groote Schuur Hospital in Cape Town, South Africa between July 2013 and July 2018. Overall survival (OS) and disease‐free survival (DFS) were evaluated using the Kaplan–Meier method. Cox proportional hazards modeling analyzed patient and treatment factor associations with survival. Logistic regression modeling was performed to assess factors associated with the receipt of chemotherapy and baseline hemoglobin. Results Among 278 patients, 28.4% (n = 79) of women had co‐infection with HIV, and 64.8% (n = 180) received chemoradiation. Regardless of HIV status, patients who received chemoradiation had improved 2‐year OS (87.4% vs. 52.8%, p < 0.001) and DFS (80.2% vs. 58.3%, p < 0.001) compared to those receiving radiation alone. Factors associated with improved OS were receipt of chemotherapy (HR 0.32, p = 0.005) and higher baseline hemoglobin (HR 0.86, p = 0.018). Upon multivariate logistic regression, adjusting for age, stage, and HIV status, patients with stage III/IV disease were less likely to receive chemotherapy (HR 48.17, p < 0.001) and were less likely to have hemoglobin ≥ 10 g/dL (HR 0.20, p < 0.001). Conclusions Addition of chemotherapy to standard radiation improved OS in women with LACC, regardless of HIV status. Our findings add to a body of literature highlighting the importance of providing concurrent chemoradiotherapy to all patients with LACC, including persons living with HIV and those with stage III/IV disease.